Detection, identification and live/dead differentiation of the emerging pathogen Enterobacter sakazakii from infant formula milk and the processing environment - Cawthorn, Donna-Maree (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2007.